Complex Magnetic Nanostructures Synthesis, Assembly and Applications - Sharma, Surender Kumar; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book offers a detailed discussion of the complex magnetic behavior of magnetic nanosystems, with its myriad of geometries (e.g. core-shell, heterodimer and dumbbell) and its different applications. It provides a broad overview of the numerous current studies concerned with magnetic nanoparticles, presenting key examples and an in-depth examination of the cutting-edge developments in this field. This contributed volume shares the latest developments in nanomagnetism with a wide audience: from upper undergraduate and graduate students to advanced specialists in both academia and industry. The first three chapters serve as a primer to the more advanced content found later in the book, making it an ideal introductory text for researchers starting in this field. It provides a forum for the critical evaluation of many aspects of complex nanomagnetism that are at the forefront of nanoscience today. It also presents highlights from the extensive literature on the topic, including the latest research in this field.
Chapter 1: Granular magnetic nanostructures -- Chapter 2: Size and Shape controlled liquid phase synthesis of magnetic nanoparticles -- Chapter 3: Bimagnetic soft/hard and hard/soft magnetic core-shell nanoparticles with diverse application -- Chapter 4: Magnetic nanoparticles probed by synchrotron radiations based on X-ray absorption method -- Chapter 5: Bimetallic nanostructures with magnetic and noble metals -- Chapter 6: Design of rare-earth doped iron oxide nanomaterials for future possibility in resonance imaging -- Chapter 7: Magnetic Nanohybrids for the water purifications -- Chapter 8: Superparamagnetic composite based GO/rGO for the multimode biomedical applications -- Chapter 9: Magnetic nanoparticle-based hyperthermia for cancer treatment -- Chapter 10: Functionalized Magnetic nanohybrids structures for imaging and therapy applications.
Keywords: Nanotechnology; Nanoscience; Magnetism; Nanochemistry; Nanotechnology; Nanophysics; Magnetism; Nanochemistry